Relationship between home learning facilities and student learning motivation and learning achievement in light vehicle engine maintenance - Johan, Arif Bintoro; Anggi Resta Rinaldi; Hidayatulloh, Rosyid Shidiq (Universitas Sarjanawiyata Tamansiswa, 2024)
The study aims to find out the relationship between home learning facilities and learning motivation with the learning achievement of engine vehicle maintenance either individually or collectively. This research is an ex-post facto study with a quantitative approach using correlational research methods. Sampling technique using the total sample or involving the entire population is as many as 44 students. The research instrument used is a questionnaire. The results of the study used data analysis techniques using partial correlation analysis and double regression analysis preceded by prerequisite tests,. multicolinearity tests, normality tests, and linearity trials. Based on the results of the research that has been carried out, found the R Square value of 67.4% where home learning facilities have an effective contribution of 26.3% and learning motivation of 41.1%. Whereas the partial correlation analysis shows X1 (3,134) and X2 (4,532) > 1,68288 and the double regression analysis shows 42,359 > 3,32 with a significance value below 0.05 that is 0,000 so it can be concluded that there is a positive and significant relationship between home study facilities and study motivation with the learning achievement of engine vehicle maintenance either individually or collectively.